KONTRIBUSI REKRUTMEN SERTA GAJI TERHADAP RETENSI PEGAWAI RSU NURHAYATI GARUT - Avicena Farhan Ramadhan; Acep Rohendi; Yani Restiani Widjaja (Journal of Innovation Research and Knowledge, 2026)
This study aims to determine and analyze the influence of recruitment and salary on employee retention at Nurhayati Garut General Hospital. The high employee turnover rate and salary discrepancy are the main reasons for this study. The research method used is descriptive quantitative. The population in this study amounted to 300 people with a sample of 172 respondents taken using a simple random sampling technique. Data analysis was carried out using multiple linear regression with the help of SPSS 24. The results showed that partially recruitment and salary have a significant effect on employee retention. Simultaneously, recruitment and salary contribute an influence of 87.4% to employee retention, while the rest is influenced by other factors